Bone marrow aplasia in B cell chronic lymphocytic leukaemia: successful treatment with antithymocyte globulin. Issue 11 (November 1991) - Singal, R; Winfield, D A; Greaves, M
Abstract : Pure red cell aplasia is a rare but well known association of chronic lymphocytic leukaemia (CLL). Pancytopenia due to bone marrow aplasia has not been previously described in CLL. A 42 year old man with B cell CLL became severely pancytopenic with bone marrow aplasia. Bone marrow culture resulted in a greatly reduced colony formation. High dose corticosteroids and intravenous immunoglobulin treatment were unsuccessful. Prompt and complete marrow recovery ensued after administration of antithymocyte globulin.